PERANAN KOMUNITAS INTELIJEN DAERAH DALAM PERMASALAHAN PERSEBARAN JEMAAH AHMADIYAH INDONESIA DI KOTA SUKABUMI - Peri Irawan; Agustina Setiawan; Dahly Sukmapryandhika Ar (Universitas Jenderal Ahmad Yani, 2017)
The role of Kominda as eyes and earsin carry out early warning and early detection to threat, interference, resistance and challange in the region isvery existance necessery. That case do aseffort to keep stability region so that the threat, interference, resistance and challange appears may pressed since early by the certain sequence and methode. The existance of Jemaah Ahmadiyah Indonesia in area of Sukabumi city is considered astray by the religious Majelis Ulama Indonesia number : 11/MUNAS VII/MUI/15/2005 and another rule release by the side of Indonesian government related banned of Jemaah Ahmadiyah Indonesia dispersion there are SKB 3 Menteri Tahun 2008 No. Kep : 033/JA/6/2008 about command and warming to the member or followers Jemaah Ahmadiyah Indonesia become one case of attention bye the Sukabumi citys government. Passed of Kominda as one of region government instrument effortssome early handling prosses for burst of problem both for happened or will be happen as a form anticipation and prediction, but the prosses have constrain from the facilities and basic facilities which used by Intelligent who moved in the ground. However that case unaffect the quality of performance of Kominda.